Effect of Ionic Liquid on Separation and Purification of Tea Polyphenols Using Counter Current Chromatography - Chen, Xiaofen; Huang, Xinyi; Wang, Gaohong; Zhang, Jia; Di, Duolong (Asian Journal of Chemistry, 2014)
In order to research the effect of ionic liquid as additives in two-phase solvent system on the behaviour of counter-current chromatography and develop more efficient methods of preparative separation and purification for natural products, a series of imidazolium-based ionic liquids with anion of [BF4]– (1-methyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate) and four structurally similar tea polyphenols ((-)-epigallocatechin-3-gallate, (-)-epicatechin, (-)-epicatechin-3-gallate, (-)-gallocatechin gallate) were, respectively chosen as additives and model molecules. The results showed that with the additive of 0.6 mol/L [MMIM][BF4] in ethyl acetate-water solvent system, the K values of (-)-epicatechin-3-gallate could drop from 30.46 to 3.47. The process of screening solvent systems based on ionic liquids was simpler and more efficiency than traditional ways. Subsequently, IR and NMR spectrum were performed to investigate the interactions between tea polyphenols and ionic liquids. It was considered that the major interaction between ionic liquid and target compounds was electrostatic attraction.